TRATKUL Solusi Cerdas Pakan Alternatif Peningkat Kualitas dan Kuantitas Telur Itik - Nugraeni, Utami; Rahmawati, Kurnia; Febrina TUE, Risfi; Diyanah, Siti Mustamatud; Saha, Muhammad Agni (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Conch field / kakul a rice crop pest found in many parts of Indonesia, especially the paddy Cilacap. Keong more widely known as pests, in addition to the rice snail belonged to a water snail intermediate host Fasciola sp, the flatworm species that attacks the liver rather the duct biliverus ruminants (cattle, sheep, goats) However, paddy snails actually have very good nutrition if used properly, for example by providing rice field snails to ducks as an adjunct feed. With fairly high protein content, giving the rice field snails can provide addition of muscle mass, as well as an increase in reproductive hormones that will stimulate the improvement in quantity and quality of duct eggs. Contains nutrients intact with snail snail paddy rice has been processed to have differences. Conch rice has been processed to have a higher protein content. With so many complaints from farmers on rice field snails as well as opportunities for the utilization of plant pests such as duck feed rice in Indonesia, particularly in the Cilacap region is quite high, so we are motivated to make a PKM-K with the title "TRATKUL" Smart Solutions Enhancing Quality and Alternative feed for duck egg quantity, in order to create market demand for alternative feed that can improve the quality and production of duck eggs, as well as being answered unrest rice pests farmers will be quite difficult in this exterminate. Efforts to increase the quality and quantity of duck eggs and the creation of new alternative feed source is a business that is currently in great demand by many in Indonesia, particularly in the area of Cilacap. Because the reality of the community and the many fans of duck eggs or duck duck meat but the amount does not meet the market demand and the high price. With presence TRATKUL expected to deliver real results to the increase of weight quickly ducks and improving the quality and quantity of eggs that meet the needs of market will duck meat and duck eggs, as well as the utilization of the rice plant pests very detrimental to farmers. And of course create new jobs for the people of Indonesia, especially Cilacap. The method in this effort using two steps, namely : 1) Making and marketing TRATKUL with production houses in Maos Kidul, Maos, Cilacap,Central Java, 2) Preparation of small-scale duck farms as feed quality evidence TRATKUL with indications the number and quality of eggs produced and live weight gain of ducks. Keywords : Tratkul,Hospes,Analisis Proximat